Foresight Study on the Adoption of Autonomous Robots for Parcel Delivery - Shaharudin, Sasha Afiza Amira; Salim, Siti Aisyah (Research in Management of Technology and Business, 2023)
The use of innovative technology like autonomous robots is important as consumers become more demanding and expect to get faster delivery from the seller. This has urged the parcel delivery industry to provide better and efficient services to customers. However, the current delivery services are still getting complaints including late delivery, unacceptable condition of goods received and poor customer service. Further, the issue of failure to deliver parcels on time is a big problem among consumers who had experience using services delivery in Malaysia. One of the inventions created to solve these problems is through the adoption of autonomous robot technology for parcel delivery (ADR). Thus, this study aims to determine the key drivers as well as finding the future trends of the adoption of ADR in Malaysia. A mixed method approach which consists of STEEPV and quantitative study have been used in this research. There are ten factors that have been merged from the STEEPV method. The data has been analyzed using Statistical Package for Social Science (SPSS) software. Impact uncertainty is analyzed based on the key drivers and issues from the qualitative and quantitative methods. Ten merged key drivers and issues have been identified. The impact-uncertainty analysis approach had been used to identify the future trends of autonomous robots’ adoption. 30 questionnaires had been distributed to consumers who had experience using conventional methods of delivery in Malaysia with response rate 42.19%. This study found that using autonomous robots to deliver packages can save money and autonomous robots for parcel delivery can prevent theft as it has a robust detecting mechanism that has the highest impact and uncertainty. Four scenarios were proposed at the end of the study. The four scenarios were new advancement, lost trust in autonomous robot technology, cyber security risk and high demand autonomous robots.